(untitled) - Spear, Terry (Naperville, Illinois, 2022)
"After fleeing from the Arctic wolf pack leader who turned them, David Davis and his friends traveled to the wilds of Minnesota to find their new home. David never would have managed to free himself without the help of daring she- wolf Elizabeth Simpson, who never left his side while they were on the run. But when Elizabeth discovers her grandmother is dying, she makes the heartbreaking decision to return to the Northwest Territories to be with her in her final days. Theres no guarantee shell be able to escape again, or that their vengeful former packmaster wont come after them if she does. But one thing is for certain--David will not give up until Elizabeth is back in his arms"--
Keywords: Man-woman relationships; Fiction; Werewolves; Fiction; Minnesota; Fiction; Werewolf fiction; Romance fiction; Paranormal fiction; Fiction